Studi Kasus Pengambilan Keputusan Orang Tua Berekonomi Rendah Dalam Memilih Sekolah Bagi Anak Di Sd Muhammadiyah 21 Baluwarti - Rahmawan, Pradhita Wisnu Dwi; , Dra. Sri Hartini, S.H., M.Pd (2016)
This study aims to identify: 1) the factors behind parents in choosing schools for children in SD Muhammadiyah 21 Baluwarti; 2) The role of school fees at the decision of parents in the selection of SD Muhammadiyah 21 Baluwarti as school children; 3) The role of religious education curriculum that the school applied to the decisions of parents in choosing SD Muhammadiyah 21 Baluwarti as school children. This type of research used is qualitative research combined with case study research design. Informants in this study are the parents of grade 1 students with the characteristics of low economic class as the key subject and Principal of SD Muhammadiyah 21 Baluwarti. Data collection techniques are implemented is the observation (participatory), interview (indept interview) and documentation (photos). Once the data is collected, then analyzed by the method of data reduction and formulate conclusions. Mechanical inspection data is done in three ways, triangulation of sources, methods and theories. The results showed that there are several factors that underlie the parents in choosing SD Muhammadiyah 21 Baluwarti as school children. The final results of this study concluded the cost factor and curriculum religious education as a major factor behind the low economic decisions of parents in choosing schools at SD Muhammadiyah 21 Baluwarti.